HAJIKU BUDAYAKU: SEBUAH SEMIOTIKA BUDAYA DI SAMARINDA - Khasanah, Anisatun; Akhlak, Annisa; Safitri, Imelda Intan (Fakultas Ilmu Budaya, Universitas Mulawarman, 2017)
The Hajj is the fifth in pillars of Islam which has special meaning for Moslem in Indonesia, especially in Samarinda. Cultures in Samarinda surely influences the large numbers of hajj applicants in this city. Thus cultures affect the high number of hajj waiting applicants in Samarinda. Performing Hajj has been impure which can be seen from some symbolic aspects that are meaningful, mystic, and contemplative. This phenomenon can be analyzed by a study named cultural semiotic. This research is purposed to reveal symbolic meanings of hajj in Samarinda’s society. The method which is used is the deep interview to 12 interviewees who have ever performed Hajj in Samarinda Seberang, Sungai Pinang, and Samarinda Kota. The result is there are five cultures that encourage Samarinda’s people in performing Hajj, and there are 5 relations between hajj status and social status in Samarinda.Keywords: the hajj, culture, semiotic, Samarinda